Approach to Human Capital in National Postal Providers: A Cross-country Analysis in Europe - Gottwald, Dalibor; Zákorová, Eva; Švadlenka, Libor; Pavlisová, Hana (Promet - Traffic&Transportation, 2018)
The article investigates human capital in national postal providers (NPPs), which is an area that has yet to be underpinned by research. There is a number of works dealing with human capital, but only few address human capital in the postal service sector. The main aim of the article is to define differences in approach to human capital management in selected NPPs. Differences are expressed via the overall Human Capital Index (HCI). Due to the fact that so far there has been no complex research analyzing activities related to human capital in NPPs, it was necessary to carry out a content analysis of annual reports of selected NPPs. Results of the analysis served as a basis for expression of overall HCI. This study brings new insights into the topic and contributes to the sustainable development of the field.